IMPERATIVE POLITENESS STRATEGIES IN TEACHING OF ENGLISH - Suswanto Ismadi Megah (Universitas Riau Kepulauan, 2012)
Teaching of English is not merely transfer knowledge about a language, esecially English but it also transfer knowledge more than only a language. We always think about teachers and what they do in front of the classroom while teaching, without thinking about: What do the students know , what is English, what motivates student , how do students learn. Whereas we know the process of teaching English language teachers must have an appropriate strategy so that students interested in following the lesson to be conveyed by the teacher. This study concerns how the English teacher teaches politely in front of the classroom in order to make the students more confortable to achieve the material of the teacher. The imperative politeness strategies used in teaching English normally by the English teacher will use “please” to soften the instruction more polite. This is aimed to make an example that the teacher does politely so the students are easy to follow becaue the teacher preserve the students face. In addition, the teacher can use past tense “would” compareed “will” in request to the students.